2004
DOI: 10.1016/j.ejcts.2004.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pleural effusion pH on the efficacy of thoracoscopic mechanical pleurodesis in patients with breast carcinoma

Abstract: TMP is a safe palliative treatment for MPE in breast carcinoma, with a minimal number of complications and a short hospital stay; it is more successful than TP in patients with pH of MPE below 7.3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 19 publications
0
36
1
5
Order By: Relevance
“…There are several contributory causes for this. First, the present data are presented using intention-to-treat analysis, a method used by only a few of the other authors [17][18][19]. This implies that patients with a contraindication for pleurodesis after positioning of the drain are included in the denominator of the success rate calculation.…”
Section: Discussionmentioning
confidence: 99%
“…There are several contributory causes for this. First, the present data are presented using intention-to-treat analysis, a method used by only a few of the other authors [17][18][19]. This implies that patients with a contraindication for pleurodesis after positioning of the drain are included in the denominator of the success rate calculation.…”
Section: Discussionmentioning
confidence: 99%
“…Still, VATS treatment can effectively shorten the amount of time during which patients require chest tube drainage as shown in the present study, and thus the overall expense can be less. Previous literature has shown that VATS treatment is more effective than tube thoracostomy for patients with an MPE pH of less than 7.3 [25].…”
Section: Original Thoracicmentioning
confidence: 98%
“…Bir çalışmada plevral sıvı pH'nın survi üzerine etkisi belirleyici olmamakla birlikte, başarısızlığı belirlemede daha önemli olduğu saptanmıştır (61). Bir başka ça-lışmada pH 7.3'ün altında olduğunda mekanik plörodezin talktan daha başarılı olduğu gösterilmiştir (62).…”
Section: Plöredez Başarısını Etkileyen Faktörler Nelerdir?unclassified
“…Meme kanserli hastalarda yapılan bir çalışmada pH'nın 7.3'ün üstünde olduğu hastalarda talk plörodez ile torakoskopik mekanik plörodez arasında başarı farkı saptanmazken, pH 7.3'ün altına düştüğünde torakoskopik mekanik plörodezin daha başarılı olduğu bulunmuştur (62).…”
Section: Plöredez Başarısını Etkileyen Faktörler Nelerdir?unclassified